EMOTIONAL INTELLIGENCE AND TRANSFORMATIONAL LEADERSHIP OF GYMNASIUM TEACHERS’ - Peciuliauskiene, Palmira (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article deals with the associations of transformational leadership of gymnasium teachers’ and their emotional intelligence. The operationalization of the concept of emotional intelligence in this study is viewed as the interaction of four determinants: Self-Emotional Appraisal (SEA); Others’ Emotional Appraisal (OEA); Regulation of Emotion (RE); Use of Emotion (UE). The aim of the article is to explore how profile gymnasium teachers’ transformational leadership is associated with their emotional intelligence dimensions. Wong and Law’s Emotional Intelligence Scale (WLEIS) was used to measure the emotional intelligence of gymnasium teachers. Multifactor Leadership Questionnaire (MLQ) was used in the research of leadership expression. The collected data were analyzed using structural equation modelling (SEM). The findings confirm that the transformational leadership is statistically significantly associated with emotional intelligence of gymnasium teachers from Lithuania. SEM analysis revealed that the use of emotions is statistically significantly associated with gymnasium teachers’ transformational leadership.